Dinamika Intrepetasi dan Penanganan Perbuatan Melawan Hukum Oleh Pemerintah - Anggita Sukmajati; Rizky Kurnia Mahardhika; Kukuh Satria Wiratama; Reynaldi Jodi Witardi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Unlawful acts are things that often occur, where people can be said to be against the law if they take actions that cause harm to other parties who feel aggrieved.In actualizing it in our lives, not infrequently those who do this are governments that should have an obligation to protect their people as mandated by us. In practice, if the government is proven to violate applicable regulations, as citizens we can sue in the form of a lawsuit to the competent court, namely the State Administrative Court which is competent to resolve administrative claims. In its development, enforcement in terms of government administration has occurred several times in the surge or dynamics of interpretation where there are changes or differences in views that are adjusted to the legal views in our country.